Reduced graphene oxide deposited carbon fiber reinforced polymer composites for electromagnetic interference shielding. (March 2016) - Chen, Juan; Wu, Jiaming; Ge, Heyi; Zhao, Dan; Liu, Cong; Hong, Xiufeng
Abstract: Reduced graphene oxide deposited carbon fiber (rGO-CF) was prepared by introducing GO onto CF surface through electrophoretic deposition method, following by reducing the GO sheets on CF with NaBH4 solution. The rGO-CF was found to be more effective than CF to improve the electromagnetic interference (EMI) shielding property of unsaturated polyester (UP) based composites. With 0.75% mass fraction of rGO-CF, the shielding effectiveness of the composite reached 37.8 dB at the frequency range of 8.2–12.4 GHz (x-band), which had 16.3% increase than that of CF/UP composite (32.5 dB) in the same fiber mass fraction. The results suggest that rGO-CF is a good candidate for the use as a light-weight EMI shielding material.